Batoclimab as an add‐on therapy in neuromyelitis optica spectrum disorder patients with acute attacks. (25th September 2022) - Wang, Yuge; Zhong, Xiaonan; Wang, Honghao; Peng, Yu; Shi, Fudong; Jia, Dongmei; Yang, Huan; Zeng, Qiuming; Quan, Chao; ZhangBao, Jingzi; Lee, Michael; Qi, Jun; et al.
Abstract: Background and purpose: Neuromyelitis optica spectrum disorder (NMOSD) is a severe neurological inflammatory disease mainly caused by pathogenic aquaporin‐4 antibodies (AQP4‐IgG). The safety and efficacy of the neonatal Fc receptor antagonist batoclimab addition to conventional intravenous methylprednisolone pulse (IVMP) therapy in patients with NMOSD acute attacks was assessed. Methods: In an open‐label, dose‐escalation phase 1b study, NMOSD patients with acute myelitis and/or optic neuritis received four doses of weekly subcutaneous injections of either 340 mg or 680 mg batoclimab with concurrent IVMP and were followed up for 27 weeks. The primary end‐points were safety and tolerability. Secondary end‐points included pharmacodynamics and efficacy, with key efficacy assessment at week 4. Results: In total nine NMOSD patients were enrolled, including two and seven in the 340 and 680 mg groups. Five patients had acute myelitis, while the remaining four had unilateral optic neuritis. Batoclimab add‐on therapy had an overall good safety profile without serious adverse events. In the 680 mg group, mean immunoglobulin G (IgG) reached its maximum reduction at the last dose (day 22). In the meantime, AQP4‐IgG was undetectable in six of seven subjects whose baseline AQP4‐IgG titers ranged from 1:32 to 1:320. Expanded Disability Status Scale score was reduced by 1.3 ± 0.4 at week 4 (2.7 ± 1.3) compared with baseline (4.0 ± 1.0). Conclusions: Batoclimab add‐on therapy to IVMP is safe and tolerated in patients with NMOSD. Preliminary evidence suggests a beneficial neurological effect. A randomized controlled trial would be needed to prove the efficacy. Abstract : The safety and efficacy of neonatal Fc receptor antagonist batoclimab addition to conventional intravenous methylprednisolone pulse therapy in patients with acute attacks of neuromyelitis optica spectrum disorder (NMOSD) were assessed. Batoclimab add‐on therapy had an overall good safety profile without serious adverse events. An initial efficacy signal of Expanded Disability Status Scale improvement was also observed, indicating a potential therapeutic benefit in patients with acute attacks of NMOSD.